The Influence of the Quality of Human Resources and the Quality of Public Services on Public Satisfaction in Patamuan District, Padang Pariaman Regency - Syahdila, Helma; Syamsir (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research seeks to examine the impact of human resource quality and public service quality on public satisfaction levels in Patamuan District, Padang Pariaman Regency. It employs a quantitative method with an associative approach. The study population consists of individuals who access services at the Patamuan District Office, with a sample of 90 respondents gathered via questionnaires and analyzed through multiple linear regression using SPSS version 25. Findings reveal that human resource quality exerts a positive and significant effect on public satisfaction, evidenced by a significance value of 0.031 (< 0.05) and a contribution of 52.1%. Similarly, public service quality shows a positive and significant influence on satisfaction, with a significance score of 0.047 (< 0.05) and a contribution of 44.0%. Collectively, both factors significantly affect public satisfaction, as indicated by an Adjusted R Square of 0.607 (60.7%), while the remaining 39.3% is attributable to variables beyond this study. These outcomes suggest that enhanced human resource quality in terms of capabilities, knowledge, and skills along with improved service delivery that is prompt, precise, and courteous, leads to higher public satisfaction with government services. Consequently, ongoing efforts to boost the competence and professionalism of officials, as well as refine the public service framework, are essential to make services in Patamuan District more effective, efficient, and focused on community satisfaction.